2022
DOI: 10.1002/jssc.202200283
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phenolic resin core‐shell structure derived carbon microspheres for ultrafast magnetic solid‐phase extraction of triazine herbicides

Abstract: In this study, monodisperse magnetic carbon microspheres were successfully synthesized through the carbonization of phenolic resin encapsulated Fe3O4 core‐shell structures. The magnetic carbon microspheres showed high performance in ultrafast extraction and separation of trace triazine herbicides from environmental water samples. Under optimized conditions, both the adsorption and desorption processes could be achieved in 2 min, and the maximum adsorption capacity for simazine and prometryn were 387.6 and 448.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Jouybari et al [5] established a novel hydrophobic deep eutectic solvent-based dispersive liquidliquid microextraction technique combined with HPLC for the determination of THs residues in fruit and vegetables with the enrichment factor (EF) in the range of 128-155. Pan et al [6] employed monodisperse magnetic carbon microspheres as magnetic solid-phase extraction (MSPE) adsorbent in combination with HPLC for the analysis of THs in environmental water samples with limits of detection (LODs) in the range of 0.30-0.41 ng/mL. Wang et al [7] reported the extraction of THs from rice with pipette tip-SPE using phosphoric acid-activated charcoal modified by chitosan as adsorbent before HPLC, and the LODs were 1.41-3.35 ng/g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jouybari et al [5] established a novel hydrophobic deep eutectic solvent-based dispersive liquidliquid microextraction technique combined with HPLC for the determination of THs residues in fruit and vegetables with the enrichment factor (EF) in the range of 128-155. Pan et al [6] employed monodisperse magnetic carbon microspheres as magnetic solid-phase extraction (MSPE) adsorbent in combination with HPLC for the analysis of THs in environmental water samples with limits of detection (LODs) in the range of 0.30-0.41 ng/mL. Wang et al [7] reported the extraction of THs from rice with pipette tip-SPE using phosphoric acid-activated charcoal modified by chitosan as adsorbent before HPLC, and the LODs were 1.41-3.35 ng/g.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al. [6] employed monodisperse magnetic carbon microspheres as magnetic solid‐phase extraction (MSPE) adsorbent in combination with HPLC for the analysis of THs in environmental water samples with limits of detection (LODs) in the range of 0.30–0.41 ng/mL. Wang et al.…”
Section: Introductionmentioning
confidence: 99%